Perception of patients towards the role of pharmacist: a cross‐sectional study from selected three hospitals in Central Nepal. Issue 2 (26th February 2018) - Shrestha, Shakti; Poudel, Ramesh Sharma; Thapa, Priyanka; Baniya, Susmita; KC, Bhuvan
Abstract: Objectives: To determine the perception of patients towards pharmacist and factors affecting their choice of pharmacy in hospitals of central Nepal. Methods: A prospective cross‐sectional study was conducted among outpatients ( n = 400) of three different purposively selected hospitals of Bharatpur, Nepal, using a systematic random sampling technique. Information on socio‐demographic features, patient's description about pharmacist, frequency of interaction with pharmacist, reason for interaction, factors affecting the choice of pharmacy and patient's perception towards the role of pharmacist were collected. Descriptive statistics were calculated and chi‐squared test was used to determine the association of patient's perception and factors influencing choice of pharmacy with socio‐demographic variables. Key findings: Of 400 participants, majority (45.5%) believed that pharmacists have knowledge and information about medicines and their use. Most patients (213, 53.3%) interacted rarely with pharmacist, and most common reasons for interaction were queries about drug dosage (242, 60.5%) and drug availability (110, 27.5%). The overall perception of patients towards the role and responsibilities of pharmacist was positive, and most of the perception was associated with socio‐demographic variables. Efficient communication (399, 99.7%) and appropriate counselling on side effects (397, 99.2%) were two major factors that determined the selection of pharmacy by the patients. Conclusion: The overall perception of patients towards pharmacist was positive in central Nepal. However, misconceptions still persist. Selection of pharmacy in our setting was mainly based on effective communication and proper counselling on side effects.